New soliton solutions for Kaup-Boussinesq system - Najafi, Houshang; Najafi, Malihe; Arbabi Mohammad-Abadi, Somayeh (International Journal of Applied Mathematical Research, 2012)
In this Letter, we study Kaup-Boussinesq system by using the well-known He's variational approach. In fact, the He's variational method is a promising method to various systems of linear and nonlinear equations.